Las metamorfosis de la racionalidad capitalista: egoísmo, sufrimiento y beneficio Miguel A. V. Ferreira. 2025. Madrid. Catarata. 284 pp - Sosa Erdozain, Gonzalo (Política y Sociedad, 2025)
Book review of: The capitalist rationality metamorphoses: benefit, suffering and profit. Miguel A. V. Ferreira. 2025. Madrid, Catarata, 284 pgs.